THE EFFECT OF FINANCIAL COMPENSATION AND NON-FINANCIAL COMPENSATION ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Rahmawati, Eva; Rahman, Taufikur (Journal of Islamic enterpreneurship and Management, 2022)
This study aims to examine the effect of financial and non-financial compensation on employee performance with job satisfaction as an intervening variable. The data collection method in this study was by distributing questionnaires to 50 employees of Bank Bukopin Syariah KC Surakarta. This study uses a saturated sample technique. The research used Analysis with reliability test, classical assumption test, t test, and path analysis test (path analysis). The results of the t test show that financial and non-financial compensation, and job satisfaction have a positive and significant effect on employee performance. The F test shows that financial and non-financial compensation and job satisfaction simultaneously have a positive and significant effect on employee performance with an influence of 86.2%, the remaining 13.8% is influenced by other variables outside the model. Based on the path analysis test, it shows that financial and non-financial compensation have a positive and significant effect on employee performance through job satisfaction as an intervening variable.